Influence of the SiC content and sintering temperature on the microstructure, mechanical properties and friction behaviour of sintered self-lubricating composites. (19th October 2016) - Binder, C.; Bendo, T.; Pereira, R. V.; Hammes, G.; de Mello, J. D. B.; Klein, A. N.
Abstract : This work reports the development of a new, low-friction coefficient combined with high mechanical strength and scuffing resistance of self-lubricating composite produced by powder injection moulding process and the recently introduced plasma-assisted debinding and sintering process. We present and discuss the effect of sintering temperature and SiC content on the microstructure, mechanical and friction properties. Three different temperatures (1100, 1150, 1200°C) and six different SiC contents (0–5%) were analysed. SiC content had a paramount role on the microstructure, mechanical and friction behaviour. Sintering temperature had almost no effect on the friction coefficient. However, the sintering temperature strongly influences scuffing resistance. Raman spectra obtained in the central region of the wear scar indicate the presence of turbostratic two-dimensional graphite. The misorientation between graphene planes and the increase in interlamellae distance may induce a low interaction between these atomic planes and are, probably, the origin of the low-friction coefficient.